A case study on the factors that influence customer acceptance towards Islamic banking system in Malaysia / Ahmad Fittri Azmi - Azmi, Ahmad Fittri (Faculty of Business and Management, 2011)
Malaysia is one of the Muslim countries that is committed in not only developing Islamic banking system but also a complete Islamic financial system. The Islamic banking system in Malaysia started in 1983 when the first Islamic bank, Bank Islam Malaysia Berhad (BIMB) commenced its operations. It was the objective of the Malaysian government to develop the Islamic banking system parallel to the conventional system. Instead of establishing many new Islamic banks, the government introduced a concept of ‘Islamic window’ which allows the existing conventional banks to introduce Islamic banking products of customers. The concept of Islamic window started in March 1993 when the Central Bank of Malaysia or Bank Negara Malaysia (BNM) introduced the “Interest-Free Banking Scheme”. Twenty-one Islamic financial products were developed to cater for this scheme with only three major banks participated initially. By July of the same year, this scheme was extended to all financial institutions in Malaysia. As at end of 2000, the Islamic banking system was represented by two Islamic banks, 17 domestic commercial banks, five merchant banks and seven discount houses. There are also four foreign-owned banks providing Islamic banking products and services.